2004
DOI: 10.1029/2003gl018882
|View full text |Cite
|
Sign up to set email alerts
|

WWLL global lightning detection system: Regional validation study in Brazil

Abstract: [1] An experimental lightning detection network, the World Wide Lightning Location network (WWLL), is being developed to provide real time global coverage with 10 km location accuracy and at least 50% detection efficiency. This paper provides a ''worst case'' analysis of WWLL location accuracy in Brazil where the VLF lightning receivers that make up the network are very distant (>7000 km). Through comparison to a local lightning detection network, we analyze the detection accuracy in Brazil with respect to tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 18 publications
5
142
1
2
Order By: Relevance
“…The handling practice for the WWLLN data used in this paper ensures that the time residual for the data collected (indicating the quality of the fit to the data) is less than 30 µs and that the lightning strokes are detected by at least five WWLLN VLF receiver stations (Rodger et al, 2009). This protocol differs from some previous studies that were performed early in the establishment of the network (Lay et al, 2004;Rodger et al, 2005), as comparisons to regional networks led to improvements in WWLLN data handling practices (Dr. Craig Rodger, personal communication, August 2009).…”
Section: Description Of the Wwllnmentioning
confidence: 96%
See 2 more Smart Citations
“…The handling practice for the WWLLN data used in this paper ensures that the time residual for the data collected (indicating the quality of the fit to the data) is less than 30 µs and that the lightning strokes are detected by at least five WWLLN VLF receiver stations (Rodger et al, 2009). This protocol differs from some previous studies that were performed early in the establishment of the network (Lay et al, 2004;Rodger et al, 2005), as comparisons to regional networks led to improvements in WWLLN data handling practices (Dr. Craig Rodger, personal communication, August 2009).…”
Section: Description Of the Wwllnmentioning
confidence: 96%
“…The WWLLN is a real-time, world-wide, ground-based network operated by the University of Washington that can detect strong lightning strokes occurring anywhere in the world (Dowden et al, 2002;Lay et al, 2004;Jacobson et al, 2006;Rodger et al, 2005Rodger et al, , 2006Rodger et al, , 2009. The network was initiated with the intention of achieving global detection with a location accuracy of less than 10 km (Rodger et al, 2009).…”
Section: Description Of the Wwllnmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that satellite measurements are a useful tool for estimating LNO x (Boersma et al, 2005;Beirle et al, 2010;Bucsela et al, 2010;Pickering et al, 2016). Pickering et al (2016) combined OMI V trop data with data from the World Wide Lightning Location Network (WWLLN) (Dowden et al, 2002;Lay et al, 2004;Virts et al, 2013) to estimate the production efficiency (PE) of LNO x (moles per flash). Using SPv2 and WWLLN data from the Gulf of Mexico over five Northern Hemisphere summers (2007)(2008)(2009)(2010)(2011), they obtained a mean PE value of 80 ± 45 mol flash −1 .…”
Section: Impact On Lightning No X Emissions Estimatementioning
confidence: 99%
“…The WWLLN is an experimental lightning detection network that provides the location of cloud-to-ground (CG) and some intra-cloud lightning (IC) strikes in real time. It has a global coverage with 10 km location accuracy and flash detection accuracy greater than 50 % (Lay et al, 2004). WWLLN is for the most part a time average of geo-located CG lightning flashes that cannot address the cloud-resolving characteristics of lightning.…”
Section: Data Sets and Data Assimilation System Setupmentioning
confidence: 99%